2022
DOI: 10.1038/s41746-022-00596-8
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of surgical bimanual expertise using deep neural networks in virtual reality simulation

Abstract: In procedural-based medicine, the technical ability can be a critical determinant of patient outcomes. Psychomotor performance occurs in real-time, hence a continuous assessment is necessary to provide action-oriented feedback and error avoidance guidance. We outline a deep learning application, the Intelligent Continuous Expertise Monitoring System (ICEMS), to assess surgical bimanual performance at 0.2-s intervals. A long-short term memory network was built using neurosurgeon and student performance in 156 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…With advancements in live intraoperative data acquisition for quality improvement, AI systems are believed to play a key role in mitigating adverse events and suggesting instructions in the operating room . Rolling out intelligent systems for patient care or formal postgraduate training should occur in phases and requires the same rigor of scientific practice required for pharmacologic therapies or other medical devices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With advancements in live intraoperative data acquisition for quality improvement, AI systems are believed to play a key role in mitigating adverse events and suggesting instructions in the operating room . Rolling out intelligent systems for patient care or formal postgraduate training should occur in phases and requires the same rigor of scientific practice required for pharmacologic therapies or other medical devices.…”
Section: Discussionmentioning
confidence: 99%
“…However, most participants in the skilled group primarily practiced cranial neurosurgery, and subpial resection is a fundamental technique that is mastered throughout postgraduate training . Furthermore, previously validated models trained on this sample could not only distinguish expertise but project residents’ postgraduate training year in neurosurgery . Although best practice is to compare trainee performance with quantifiable criterion standards of experts, training medical students to achieve benchmarks closer to their competency level, for example that of a junior resident, may prove more practical .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most established paradigm of this kind is surgical training [50,51]. Several studies have shown construct validity of virtual environments by differentiating among novice, intermediate, and experts based on their surgical performance in VR [52][53][54], and others have shown improvement in specific surgical skills via simulated practice [55,56]. However, these studies have not explicitly tested specific hypotheses about motor expertise.…”
Section: Box 1 Differences Between Skill and Expertisementioning
confidence: 99%
“…Additionally, the availability of high precision data streams from surgical simulation allows to automatically categorize the level of expertise of the trainee using machine learning algorithms [32]. Continuous expertise monitoring systems can further assess surgical bimanual performance in real-time, which could be leveraged to provide predictive validation during surgical residency training, allowing the early detection of errors [30] and more efficient training. Virtual reality simulators thus enable trainees to practice on a variety of educational scenarios as well as to enable the definition of new training metrics and applications (e.g.…”
Section: Introductionmentioning
confidence: 99%